ANALYSIS OF THE PUBLICATION ACTIVITY OF RESEARCH SCIENTISTS IN THE FIELD OF THEATER ART - Vasilyeva, E.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
This article is an attempt to highlight some issues related to scientometric indicators in the field of theatrical art. This area of art is well covered in various media, as it is interesting not only for professionals who have dedicated their lives to it, but for any person who is interested in one way or another in the cultural life of their country, their city. In particular, the article provides a structural analysis of articles on theatrical art over the past five years, evaluates publications by their type, identifies popular languages for publications, publications on theater studies in which authors prefer to publish their articles. In addition, the article gives a brief description of the distribution of publications of Russian authors by year. Such an analysis will help to form a general picture of the situation in the field of publishing activity in theatrical art and Russia's place in this direction. In order to conduct the assessment, the Web of Science citation database was used, which contains publications from the most influential journals in the world, including journals that are in the public domain, as well as books and conference materials. This system was used, as it is the most authoritative polythematic abstract-bibliographic and scientometric (bibliometric) database. The novelty of this study lies in the fact that the author has not been identified for the period of research in the article for publications on similar topics. However, those negative points that were identified during the study should attract the attention of scientists who are involved in the study of the development of theatrical art in Russia. The results of a deeper and more detailed analysis of this issue will be presented in our subsequent publications.